Media Application Math Board to Improve Children's Cognitiveness in RA UMDI TAQWA Parepare - Ashari, Novita (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2023)
The purpose of this study is that researchers want to apply Math Board media to increase cognitive children aged 5-6 years. This is motivated by the lack of media to develop children's cognitive aspects at RA UMDI TAQWA Parepare. The method used in this research is qualitative with a case study approach. The subjects in this study were 13 children at RA UMDI TAQWA Lakessi Parepare. The results of this study indicate that Math Board media can be an innovative media that can develop children's cognitive aspects, especially in addition and subtraction. Math Board media makes children able to solve problems and think logically with a satisfactory category because children actively participate and like Math Board, based on six indicators of children's cognitive development.